1998
DOI: 10.1046/j.1365-2958.1998.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

The permease homologue Ssy1p controls the expression of amino acid and peptide transporter genes in Saccharomyces cerevisiae

Abstract: SummaryAmino acid transporters of the yeast plasma membrane (permeases) belong to a family of integral membrane proteins with pronounced structural similarity. We present evidence that a member of this family, encoded by the open reading frame (ORF) YDR160w (SSY1), is required for the expression of a set of transporter genes. Thus, deletion of the SSY1 gene causes loss of leucine-inducible transcription of the amino acid permease genes BAP2, TAT1 and BAP3 (ORF YDR046c) and the peptide transporter, PTR2. D-leuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
215
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(230 citation statements)
references
References 36 publications
9
215
0
2
Order By: Relevance
“…To test this idea we took advantage of the fact that Put4p and Gap1p are regulated coordinately, and we found that both glutamate and cysteine could decrease Put4p activity even in a gap1⌬ strain (data not shown). Finally, Ssy1p, a recently identified amino acid sensor (37)(38)(39), and Ure2p, the proposed glutamine sensor for the nitrogen-regulated transcriptional apparatus (40,41), do not appear to be involved, because both ssy1⌬ and ure2⌬ strains exhibited a decrease in Gap1p activity when amino acids were added to the growth medium (data not shown). Further experiments are necessary to identify the proteins that transduce the amino acid signal to the Gap1p trafficking machinery.…”
Section: Discussionmentioning
confidence: 97%
“…To test this idea we took advantage of the fact that Put4p and Gap1p are regulated coordinately, and we found that both glutamate and cysteine could decrease Put4p activity even in a gap1⌬ strain (data not shown). Finally, Ssy1p, a recently identified amino acid sensor (37)(38)(39), and Ure2p, the proposed glutamine sensor for the nitrogen-regulated transcriptional apparatus (40,41), do not appear to be involved, because both ssy1⌬ and ure2⌬ strains exhibited a decrease in Gap1p activity when amino acids were added to the growth medium (data not shown). Further experiments are necessary to identify the proteins that transduce the amino acid signal to the Gap1p trafficking machinery.…”
Section: Discussionmentioning
confidence: 97%
“…Consistently, 3 of the 15 genes (AGP1, MUP1, and GNP1) of subcluster 3-1 encode amino acid permeases known to be targets of the SPS system. Five permease genes (BAP2, BAP3, PTR2, TAT1, and TAT2) in addition to AGP1, MUP1, and GNP1 have been described as SPS target genes in classical molecular studies (11,38,63,72). Although these genes also show lower expression on urea, proline, and GABA than on most of the other media, they were not classified within subcluster 3-1, as their expression profiles significantly differ from those of AGP1, GNP1, and MUP1.…”
Section: General Approachmentioning
confidence: 99%
“…Yeast regulates the import of some amino acids tightly by a system that links extracellular amino acid sensing with the function of the partially redundant transcription factors Stp1p and Stp2p. [30][31][32][33] In addition, mutations impairing amino acid sensing or Bap2p function were the only ones identified in a screen for mutations that are synthetically lethal with a leu2 mutation. 34) The STP1-constitutive allele can dramatically increase the expression of several amino acid permeases, including those that can take up leucine.…”
Section: Resultsmentioning
confidence: 99%
“…34) The STP1-constitutive allele can dramatically increase the expression of several amino acid permeases, including those that can take up leucine. 30,35) Hence we wondered whether the introduction of a plasmid encoding the STP1 constitutive allele STP1Á131 36) (see Table 2) would rescue ero1-1 leu2 cells for their growth deficiency in SC medium. As shown (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation